Clinical trial design in phase 2 and 3 trials for pulmonary hypertension. (1st November 2020) - Nikkho, Sylvia; Fernandes, Peter; White, R. James; Deng, Chunqin (CQ); Farber, Harrison W.; Corris, Paul A
Abstract : This article on clinical trial design incorporates the broad experience of members of the Pulmonary Vascular Research Institute's (PVRI) Innovative Drug Development Initiative (IDDI) as an open debate platform for academia, the pharmaceutical industry and regulatory experts surrounding the future design of clinical trials in pulmonary hypertension. It is increasingly clear that the design of phase 2 and 3 trials in pulmonary hypertension will have to diversify from the traditional randomised double‐blind design, given the anticipated need to trial novel therapeutic approaches in the immediate future. This article reviews a wide range of differing approaches and places these into context within the field of pulmonary hypertension.